A Case of Ambiguous Lineage Acute Leukemia Posing Diagnostic Challenge. (9th November 2022) - Rahman, M; Huq Ronny, F; Islam, H
Abstract: Introduction/Objective: N/A. Methods/Case Report: Acute leukemias with ambiguous lineage encompass those leukemias that show no clear evidence of differentiation along a single lineage and account for less than 4% of all cases of acute leukemias and often poses diagnostic dilemma. We present a challenging case of an ambiguous lineage acute leukemia in a previously healthy 27-year-old male, who presented to the ED with acute fever, dyspnea on exertion, nausea and vomiting. A complete blood count (CBC) showed a white blood cell count of 323 × 109/L, Hemoglobin of 3.3 g/dl, Platelet count of 44 × 10 9 /L and a differential count of Neutrophil: 11, Lymphocyte: 31, Monocyte: 02, Band Neutrophil:1, Myelocyte :1, Blast: 54. Bone marrow aspirate smears revealed a heterogenous population of small to large sized blasts comprising 83% of cellularity. They expressed scant to moderate basophilic cytoplasm, high N/C ratio, round to irregular nuclear contour, finely granular chromatin and some with nucleoli. Other lineages were markedly suppressed. Flow cytometric analysis revealed an abnormal blast population ( 80% of total) expressing CD34, HLA-DR, Tdt (subset), CD71 (dim) and CD38. In addition, the blasts expressed myeloid associated antigens CD13, MPO (smaller subset), as well as B-cell associated antigens CD19 (dim), cytoplasmic CD22 and cytoplasmic CD79a. They also expressed T-cell associated antigens, CD2, CD3 (smaller subset), CD5 (subset) and CD7 (subset) but negative for cytoplasmic CD3. This unusual pattern of expression posed a challenge as to what type of mixed phenotype leukemia it should be with variable expressions from all three lineage of myeloid, B- and T-cell. Further work-up showed, scattered blasts are also positive for MPO by cytochemical (on aspirate smear) and immunohistochemical stain (on core). The latter also showed negativity for CD3. Based on all these findings, this mixed phenotype acute leukemia (MPAL) was best categorized as MPAL (B/myeloid) over so called "Triphenotypic (B/T/myeloid) acute leukemia". We considered expression of myeloid and B cell markers as more lineage defining in this case as compared to small subset expressing T lineage marker CD3. This case exemplifies the importance of multimodal comprehensive analysis of acute leukemia, especially in the setting of MPAL with expression of multi- lineage markers posing a diagnostic challenge. Results (if a Case Study enter NA): N/A. Conclusion: N/A.